Mathematical modeling and estimation of physicochemical characteristics of pneumonia treatment drugs through a novel approach K-Banhatti topological descriptors - Abdul Rauf Khan; Ifra Naeem; Fairouz Tchier; Fikadu Tesgera Tolasa; Shahid Hussain (Frontiers in Chemistry)
IntroductionPneumonia is the primary cause of mortality in preterm infants in developing nations; yet, early detection and treatment can significantly reduce mortality rates. Pharmaceutical researchers are diligently striving to identify avariety of drugs that might effectively cure pneumonia.MethodWe are motivated to examine the quantitative structureproperty relationships (QSPR) of anti-pneumonia pharmaceuticals. We employed K-Banhatti topological descriptors and analyzed the findings to achieve this. For estimation of physicochemical properties of pneumonia treatment drugs we utilized linear, quadratic, cubic, and biquadratic regression analyses.Results and ConclusionThe drugs comprise linezolid, ceftabiprole, and clarithromycin, among others. Topological descriptors enable the exploration of the complexity, connectivity, and other essential attributes of molecules. The quantitative structure-property relationship (QSPR) analysis of pharmaceuticals for illness treatment employing K-Banhatti topological descriptors is an economical approach utilised by pharmaceutical researchers. We performed a QSPR analysis on 20 anti-pneumonia drugs to ascertain the most precise predictions for five properties: enthalpy, flash point, molecular weight, molar volume, and molar refractivity, employing five K-Banhatti indices. To do this, we used linear, quadratic, cubic, and biquadratic regression analyses to find links between molecules and the physical and chemical properties of drugs used to treat pneumonia. Employing molecular descriptors and regression models to investigate chemical patterns is a cost-effective and theoretical methodology.